2015
DOI: 10.5424/sjar/2015134-7861
|View full text |Cite
|
Sign up to set email alerts
|

Organic cultivation of field pea by use of products with different action

Abstract: The possibilities for increasing the productivity and control of the pea weevil (Bruchus pisorum L.) in field pea (Pisum sativum L.) organic cultivation by the use of following bioproducts NeemAzal T/S and Pyrethrum FS-EC (insecticides), applied individually and in combination with Polyversum (growth regulator and fungicide) and Biofa (foliar fertilizer), as well as to evaluate the stability of the used mixtures were studied. Synthetic products Nurelle D and Flordimex 420 (alone and in combination) were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We showed a significant increase in pea yield, on average by 0.5 t ha −1 , in the treatments with Polyversum WP. Our results are confirmed by experiments conducted by Georgieva et al [39], who showed that the application of the organic products Biofa, Polyversum, NeemAzal, and Pyrethrum positively influenced the productivity of forage peas. The highest yield was obtained following the application of Polyversum in combination with the bioinsecticide Pyrethrum at the budding and flowering stages.…”
Section: Wintering Yield and N Uptakesupporting
confidence: 90%
“…We showed a significant increase in pea yield, on average by 0.5 t ha −1 , in the treatments with Polyversum WP. Our results are confirmed by experiments conducted by Georgieva et al [39], who showed that the application of the organic products Biofa, Polyversum, NeemAzal, and Pyrethrum positively influenced the productivity of forage peas. The highest yield was obtained following the application of Polyversum in combination with the bioinsecticide Pyrethrum at the budding and flowering stages.…”
Section: Wintering Yield and N Uptakesupporting
confidence: 90%
“…The study of Georgieva et al (2015) showed that the use of organic products (Biofa + Pyrethrum) in field pea a, b… -Duncan's multiple range test (p < 0.05), nsnot significant For the other genotypes, higher yields were produced in the conventional production system. Performance (yield, yield stability and quality) is also linked to tolerance to abiotic and biotic stress, which is a complex of inherited traits with high genotype and environment interactions, resulting in the masking of the genotypic value of breeding lines.…”
Section: Resultsmentioning
confidence: 98%
“…Research has been conducted on optimal sowing rates (Baird et al, 2008), weed, disease and pest control (Annicchiarico, Filippi, 2008;Stanley, 2016;Georgieva, 2017), the use of organic fertilizers and stimulants in the conditions of organic production . The productivity of local and introduced cultivars and lines of peas in organic conditions (Gopinath et al, 2009;Chadha et al, 2013;Georgieva et al, 2015) was determined. Strategies, methods, technologies and protocols for organic testing and Production Guide for Organic Peas for Processing have been developed (Lammerts Van Bueren, Struik, 2004; Seaman, 2016).…”
Section: Introductionmentioning
confidence: 99%